Kraton Tegal Flats and the Struggle for Equal Housing Rights in Urban Indonesia - Rayana, Nugrahati Audia (Indonesian Journal of Agrarian Law, 2025)
This article discusses the role of Kraton Flats in Tegal City as an effort to provide housing rights that are equal to those of the lower class (MBR). In the context of urbanization, limited land, and social inequality, the construction of flats is an alternative solution that not only answers the need for housing, but also strengthens the dimensions of social justice and inclusion of urban space. Through a normative legal approach, this article analyzes how flats function as a state instrument in carrying out the constitutional mandate to provide decent, safe, and affordable housing. Kraton Flats provide basic facilities, collective living spaces, and access to social and economic services, which encourage an increase in the quality of life of its residents. However, its effectiveness is influenced by a number of supporting factors such as policy support, infrastructure quality, and citizen participation. On the other hand, there are also challenges that need to be overcome, including limited maintenance budgets, weak literacy of residents regarding rights and obligations, and social conflicts between residents. Therefore, a community-based management strategy and sustainable policies are needed so that flats truly represent the right to fair and humane housing amidst urban dynamics.